The Role of Allergens in Atopic Dermatitis - Suna Asilsoy; Serdar Al (Galenos Publishing House, 2020)
Atopic dermatitis (AD) is a chronic skin disease caused by genetic and environmental factors. Often it begins in early childhood. It is located at the first step of the process we refer to as atopic march. This feature is a precursor of the development of other allergic diseases such as asthma and allergic rhinitis. Especially in patients with atopy of food and inhalant allergens, the occurrence of other atopic diseases is more common. Although the role of these sensitivities in AD is controversial, it has been determined that some patients may trigger eczematous skin lesions. In this report, the role of allergens in atopic dermatitis are reviewed in the light of current literature.